Physicochemical Properties of Human Hair using Fourier Transform Infra-Red (FTIR) and Scanning Electron Microscope (SEM) - Obinna, Ezenwali Moses (Bumi Publikasi Nusantara, 2022)
This research work is to investigate the physicochemical properties of human hair. Data was obtained by analyzing human hair using Fourier Transform Infra-Red and Scanning Electron Microscope. Several results were obtained, including data on the chemical properties of human hair.